Assessment of Amphibians Vulnerability to Climate Change in China - Zhao, Chunlin; Jiang, Jianping; Xie, Feng; Li, Cheng; Zhao, Tian (Frontiers in Ecology and Evolution, 2022)
Global climate change is considered to be one of the main threats to organisms. As poikilothermic animals, amphibians are in particular sensitive because they cannot adapt to the dramatic climate change through active physiological regulation. Using 104 representative species, the present study conducted an assessment of amphibians vulnerability to climate change in China through the combination of two approaches. Specifically, 18 vulnerability criteria belonging to five categories (i.e., thermal tolerance, individual reproductive, population diffusion and diversity, food and habitat, and climate conditions) were first selected and scored based on literatures and experts opinions. Species were then ranked into three levels of climate change vulnerability (i.e., high, moderate, and low) by calculating vulnerability scores and conducting natural breaks analyses, as well as performing a principal coordinate analysis (PCoA) and k-means cluster analyses, respectively. To integrate the two results, a matrix with the ranks from each result was developed to produce a final integrated list. Our results indicated that the 104 amphibian species were classified into three types by natural breaks, with 54 low vulnerable species, 41 moderately vulnerable species, and nine highly vulnerable species. Based on the results of PCoA and k-means cluster analyses, five species were highly vulnerable, 38 species were moderately vulnerable, and 61 species were low vulnerable. The combination of the two ranks suggested that 36 species such as Hyla tsinlingensis and Liangshantriton taliangensis were of low vulnerability, 54 species such as Echinotriton chinhaiensis and Hynobius chinensis were of moderate vulnerability, and 14 species such as Ichthyophis kohtaoensis and Zhangixalus prasinatus were of high vulnerability. Overall, our results indicated that climate change could have strong potential effects on amphibians in China. And the highly vulnerable species such as Ichthyophis kohtaoensis, Zhangixalus prasinatus, and Theloderma corticale should be the priority in future conservation activities.